2020
DOI: 10.1002/pro.3934
|View full text |Cite
|
Sign up to set email alerts
|

TheAutoDocksuite at 30

Abstract: The AutoDock suite provides a comprehensive toolset for computational ligand docking and drug design and development. The suite builds on 30 years of methods development, including empirical free energy force fields, docking engines, methods for site prediction, and interactive tools for visualization and analysis. Specialized tools are available for challenging systems, including covalent inhibitors, peptides, compounds with macrocycles, systems where ordered hydration plays a key role, and systems with subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…For each time point, cell counts were normalized with corresponding DMSO vehicle (or PBS) -treated controls. In Alamar Blue assays, the LSD value in A549, H292, H1299, and H358 are 20 Figure S1. (C,D) Caspases -9 and -3 activities in cells treated with Hiltonol alone or polyI:C alone or Hiltonol +++ or polyI:C +++ (polyI:C+anti-IL6+stattic+AG490) for 24 h showed that Hiltonol +++ caused the highest elevation in Caspases -9 and -3 activities (red boxes).…”
Section: Hiltonol +++ Suppressed Lung Cancer Cell Proliferation Throumentioning
confidence: 99%
See 2 more Smart Citations
“…For each time point, cell counts were normalized with corresponding DMSO vehicle (or PBS) -treated controls. In Alamar Blue assays, the LSD value in A549, H292, H1299, and H358 are 20 Figure S1. (C,D) Caspases -9 and -3 activities in cells treated with Hiltonol alone or polyI:C alone or Hiltonol +++ or polyI:C +++ (polyI:C+anti-IL6+stattic+AG490) for 24 h showed that Hiltonol +++ caused the highest elevation in Caspases -9 and -3 activities (red boxes).…”
Section: Hiltonol +++ Suppressed Lung Cancer Cell Proliferation Throumentioning
confidence: 99%
“…To analyze the potential molecular interaction between Hiltonol and PKR/OAS, we performed in silico predictions by AutoDock [20] and showed the potential amino acid residues (red) involved ( Figure 6A-F). The binding structure of PKR (or OAS) to Hiltonol is shown in Figure 6B,E, respectively.…”
Section: In Silico Analysis Showed Interaction Between Hiltonol and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a molecular docking analysis between hypericin and the dimer/monomer of PEDV 3CLpro/3CLpro mut (Met6Ala, Ile151Ala, Asn152Ala, and Gln295Ala in dimer and Asn141Ala, Ile164Ala, Glu165Ala, Asp186Ala, Gln187Ala, and Gln191Ala in monomer) with AutoDock 4.2 (version 4.2.6) to predict the binding of hypericin to PEDV 3CLpro [ 31 ]. Briefly, we used 3CLpro/3CLpro mut monomer–dimer structure as a receptor (corrected it with removing co-crystallized waters and adding charges and hydrogens) and hypericin as a ligand (adding charges).…”
Section: Methodsmentioning
confidence: 99%
“…However, the antiviral activity in these large-scale screens may, in part, be cell-line specific (Hoffmann et al, 2020), and therefore of unclear clinical relevance. Another approach to screen potential drugs for repurposing is to perform docking (Goodsell et al, 2020) of clinical-stage or FDA-approved drugs to the SARS-CoV-2 proteome (S. Ortega et al, 2020). However, selection of the correct binding sites on the target proteins is crucial and difficult as protein surface cavities far exceed actual ligand binding sites that modulate function (Gupta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%